Meta-Analysis of Atrial Fibrillation Ablation in Patients with Systolic Heart Failure. (6th January 2019) - Ruzieh, Mohammed; Foy, Andrew J.; Aboujamous, Nader M.; Moroi, Morgan K.; Naccarelli, Gerald V.; Ghahramani, Mehrdad; Kanjwal, Shaffi; Marine, Joseph E.; Kanjwal, Khalil
Abstract : Atrial fibrillation (AF) and heart failure (HF) are two common conditions that often coexist and predispose each to one another. AF increases hospitalization rates and overall mortality in patients with HF. The current available therapeutic options for AF in patients with HF are diverse and guidelines do not provide a clear consensus regarding the best management approach. To determine if catheter ablation for AF is superior to medical therapy alone in patients with coexisting HF, we conducted this systematic review and meta-analysis. The primary outcomes evaluated are left ventricular ejection fraction (LVEF), Minnesota Living with Heart Failure Questionnaire (MLWHFQ) scores, 6-minute walk test (6MWT) distance, heart failure hospitalizations, and mortality. The results are presented as a mean difference for continuous outcome measures and odds ratios for dichotomous outcomes (using Mantel-Haenszel random effects model). 7 full texts met inclusion criteria, including 856 patients. AF catheter ablation was associated with a significant increase in LVEF (mean difference 6.8%; 95% CI: 3.5 – 10.1; P<0.001) and 6MWT (mean difference 29.3; 95% CI: 11.8 – 46.8; P = 0.001), and improvement in MLWHFQ (mean difference -12.1; 95% CI: -20.9 – -3.3; P = 0.007). The risk of all-cause mortality was significantly lower in the AF ablation arm (OR 0.49; 95% CI: 0.31 – 0.77; P = 0.002). In conclusion, atrial fibrillation ablation in patients with systolic heart failure is associated with significant improvement in LVEF, quality of life, 6MWT, and overall mortality.